Philosopher and Animal: Nietzsche, Heidegger, Derrida - Gutauskas, Mintautas (Problemos, 2014)
The article raises the question about the function of an animal in the philosophical discourses. One can notice that philosophers have neither competence nor intentions to investigate an animal from the viewpoint of a zoologist. However, animality has a critical role in the definition of humanity and in solving the problems of the human world and reality. The chosen philosophers show different aspects of this role. Nietzsche’s animal refers to the peculiarity of human moment, time, and historicity. Heidegger’s animal refers to the fundamental significance of language and logos in the constitution of the human world. The gaze of Derrida’s cat questions well-established anthropological difference, and returns it in form of a question. Lastly, it is maintained that animal is essential not only for the definition of human as a being with some qualitatively different attributes – reason, thought, language, shame, etc. – but also for experience of alterity. In the face of an animal, the human being finds oneself in the environment of logos and has a better understanding of his own world and of himself.